2016
DOI: 10.1002/smll.201600866
|View full text |Cite
|
Sign up to set email alerts
|

Subtissue Imaging and Thermal Monitoring of Gold Nanorods through Joined Encapsulation with Nd‐Doped Infrared‐Emitting Nanoparticles

Abstract: Encapsulation of gold nanorods together with Nd-doped fluorescent nanoparticles in a biocompatible polymer creates multifunctional nanostructures, whose infrared fluorescence allows their subcutaneous localization in biological tissues while also adding the ability to measure the temperature from the emitted light in order to better monitor the light-to-heat conversion of the gold nanorods during photothermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…To construct this kind of NP, one direct way is to combine two nanosized elements into a single nanostructure: one acts as nanoheater and the other provides thermal sensing capacity. For example, Rocha et al successfully encapsulated gold nanorods and LaF 3 :Nd NPs into single poly(lactic‐co‐glycolic acid) capsule, leading to the ability of thermally monitoring subcutaneous PTT. However, this kind of “double particle” approach increases the complexity and instability of the system.…”
Section: Therapeutic Applications Of 808 Nm‐excited Lnnpsmentioning
confidence: 99%
“…To construct this kind of NP, one direct way is to combine two nanosized elements into a single nanostructure: one acts as nanoheater and the other provides thermal sensing capacity. For example, Rocha et al successfully encapsulated gold nanorods and LaF 3 :Nd NPs into single poly(lactic‐co‐glycolic acid) capsule, leading to the ability of thermally monitoring subcutaneous PTT. However, this kind of “double particle” approach increases the complexity and instability of the system.…”
Section: Therapeutic Applications Of 808 Nm‐excited Lnnpsmentioning
confidence: 99%
“…Numerous approaches have been developed to attain highly sensitive intracellular thermometry methods, including fluorescent probes 14 18 and nanodiamonds 11 , 19 , but they are limited by spatiotemporal resolution. Spatial resolution could be improved by the encapsulation of photothermal agents with a thermometer 20 or scanning-based strategies 21 , 22 , but the detection speed keeps the temporal resolution far from the aim of imaging the transient heat generation. Integration of the photothermal material (for example, gold nanorods) and thermosensitive polymers may be the solution due to distinct photothermal properties and the mechanoresponse.…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated multimodal bioimaging by forming hybrid structures. In addition, the combination of NIR emissive Ln 3+ ‐doped UCNPs with AuNRs had shown the subtissue localization at NIR II window and thermal monitoring ability by using chicken breast tissue . These reports indicated that imaging at NIR II window might be a future trend for FI.…”
Section: Discussionmentioning
confidence: 93%